2010
DOI: 10.1037/a0018527
|View full text |Cite
|
Sign up to set email alerts
|

Ambiguity and context processing in human predictive learning.

Abstract: Two experiments explored the role of ambiguity on context processing by using relative stimulus validity designs in human predictive learning. Two groups of participants were trained with 2 stimulus compounds (XY and XZ). In Group TD (true discrimination), compound XY was always followed by the outcome, whereas compound XZ was never followed by it. In Group PD (pseudodiscrimination) the presentation of each compound was followed by the outcome in half of the trials. Experiment 1 found that pseudodiscrimination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 49 publications
2
18
0
2
Order By: Relevance
“…Second, the most recent exposition of the theory must be refined so that clear a priori predictions regarding when attention will favor one mechanism of contextual control over another can be determined. Callejas-Aguilera and Rosas (2011) have predicted an effect of a context change in these experiments, yet without further clarifications, the direction of that change cannot be specified. In the absence of that clarification, the present results are at strong odds with the one clear hypothesis offered by the theory that has been demonstrated with humans, challenging the theory's present usefulness as a general principle.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Second, the most recent exposition of the theory must be refined so that clear a priori predictions regarding when attention will favor one mechanism of contextual control over another can be determined. Callejas-Aguilera and Rosas (2011) have predicted an effect of a context change in these experiments, yet without further clarifications, the direction of that change cannot be specified. In the absence of that clarification, the present results are at strong odds with the one clear hypothesis offered by the theory that has been demonstrated with humans, challenging the theory's present usefulness as a general principle.…”
Section: Discussionmentioning
confidence: 87%
“…The theory put forth by has undergone some revision (Callejas-Aguilera & Rosas, 2011;) since its initial presentation (Rosas, García-Gutiérrez, & Callejas-Aguilera, 2006). Initially, the theory suggested that attention might engage the context through a modulator-type mechanism such as that offered by Bouton (1993), or that the context may act as an occasion setter, or that the context could enter into a configural cue such as that proposed by Pearce (1987Pearce ( , 1994.…”
Section: Discussionmentioning
confidence: 99%
“…That is, the overall uncertainty associated with the AB compound is lower than that associated with the CD compound, and so²on the basis of the idea (raised earlier) that overall uncertainty may be the crucial determinant of attention (Pearce & Hall, 1980)²the uncertainty principle anticipates a reduction in attention to cues belonging to a low-uncertainty compound (A and B) relative to cues in a highuncertainty compound (C and D). 3 Other studies that are consistent with both the predictiveness and uncertainty principles have examined how attention to contexts varies as a function of the information learned in them (Abad, Ramos-Alvarez & Rosas, 2009;Callejas-Aguilera & Rosas, 2010;Gawronski, Rydell, Vervliet & De Houwer, 2010;Leon, Abad & Rosas, 2011;Nelson, Lamoureux & Leon, 2013;Rosas & Callejas-Aguilera, 2006). In essence, in these studies people initially learn that whenever Mr X eats a particular food (say steak) in restaurant R he suffers illness, but other foods eaten in this restaurant do not cause illness.…”
Section: Summary: Predictiveness Versus Uncertaintymentioning
confidence: 99%
“…For example, contextual control of behavior and thought can be achieved by instructing subjects that an event to be remembered took place in a particular location (Callejas-Aguilera & Rosas, 2010; Orinstein, Urcelay, & Miller, 2010), or by the semantic attributes of the to be remembered items, as has been documented in verbal learning (Tulving & Thomson, 1973). However, the constituents of context are not limited to the conventional sensory modalities.…”
Section: Introductionmentioning
confidence: 99%